Patient characteristics and determinants of CD4 at diagnosis of HIV in Mexico from 2008 to 2017: a 10-year population-based study - Azamar-Alonso, Amilcar; Bautista-Arredondo, Sergio A.; Smaill, Fiona; Mbuagbaw, Lawrence; Costa, Andrew P.; Tarride, Jean-Eric (AIDS research and therapy, 2021)
Background In 2007–2012 the Mexican government launched the National HIV program and there was a major change in HIV policies implemented in 2013–2018, when efforts focused on prevention, increase in early diagnosis and timely treatment. Still, late HIV diagnosis is a major concern in Mexico due to its association with the development of AIDS development and mortality. Thus, the objectives of this study were to identify the determinants of late HIV diagnosis (i.e. CD4 count less than 200 cells/mm 3 ) in Mexico from 2008 to 2017 and to evaluate the impact of the 2013–2017 National HIV program. Methods Using patient level data from the SALVAR database, which includes 64% of the population receiving HIV care in Mexico, an adjusted logistic model was conducted. Main study outcomes were HIV late diagnosis which was defined as CD4 count less than 200 cells/mm 3 at diagnosis. Results The study included 106,830 individuals newly diagnosed with HIV and treated in Mexican public health facilities between 2008 and 2017 (mean age: 33 years old, 80% male). HIV late diagnosis decreased from 45 to 43% (P < 0.001) between 2008 and 2012 and 2013–2017 (i.e. before and after the implementation of the 2013–2017 policy). Multivariable logistic regressions indicated that being diagnosed between 2013 and 2017 (odds ratio [OR] = 0.96 [95% Confidence interval [CI] [0.93, 0.98]) or in health facilities specialized in HIV care (OR = 0.64 [95% CI 0.60, 0.69]) was associated with early diagnosis. Being male, older than 29 years old, diagnosed in Central East, the South region of Mexico or in high-marginalized locality increased the odds of a late diagnosis. Conclusions The results of this study indicate that the 2013–2017 National HIV program in Mexico has been marginally successful in decreasing the proportion of individuals with late HIV diagnosis in Mexico. We identified several predictors of late diagnosis which could help establishing health policies. The main determinants for late diagnosis were being male, older than 29 years old, and being diagnosed in a Hospital or National Institute.